The Jeweled Style : Poetry and Poetics in Late Antiquity - Roberts, Michael, 1947 September 16- (Book collections on Project MUSE., 1989)
This work offers a new approach to the Latin poetry of late antiquity, one centering on an aesthetic quality common to both the literature and the art of the period--the polychrome patterning of words and phrases or of colors and shapes. In the author's view, the writer or artist of this period works as a jeweler, carefully setting compositional units in a geometric framework, consistently demonstrating a preference for effects of patterning over realistic representation, and for a unity situated at a higher level than the literal, historical sequence of the narrative. The introductory chapter is followed by an anthology of representative narrative and descriptive poetry from the fourth and fifth centuries A.D. Next, the author traces the use of 'jewels' as a literary metaphor from the first century A.D. to late antiquity. He then compares the works of late antique literature to wall and floor mosaics, ivory diptychs, Christian sarcophagi, and contemporary styles of dress. Emphasizing that the poetry of this period is not uniform, he differentiates the main genres of Christian narrative poetry--biblical and hagiographical epic--from secular examples of the jeweled style, such as the poetry of Ausonius and Sidonius. The work concludes by examining the influence of late antique aesthetics on the medieval poetics of Matthew of Vendôme and Geoffrey of Vinsauf.